A Generalized Crystallographic Description of All Tellurium Nanostructures - Kim, Min-Seok; Ma, Xing-Hua; Cho, Ki-Hyun; Jeon, Seung-Yeol; Hur, Kahyun; Sung, Yun-Mo (WILEY-V C H VERLAG GMBH, 2018)
Despite tellurium being less abundant in the Earth's crust than gold, platinum, or rare-earth elements, the number of industrial applications of tellurium has rapidly increased in recent years. However, to date, many properties of tellurium and its associated compounds remain unknown. For example, formation mechanisms of many tellurium nanostructures synthesized so far have not yet been verified, and it is unclear why tellurium can readily transform to other compounds like silver telluride by simply mixing with solutions containing silver ions. This uncertainty appears to be due to previous misunderstandings about the tellurium structure. Here, a new approach to the tellurium structure via synthesized structures is proposed. It is found that the proposed approach applies not only to these structures but to all other tellurium nanostructures. Moreover, some unique tellurium nanostructures whose formation mechanism are, until now, unconfirmed can be explained.
Keywords: ONE-DIMENSIONAL NANOSTRUCTURES; SHAPE-CONTROLLED SYNTHESIS; VAPOR-DEPOSITION ROUTE; GROWTH-MECHANISM; TRIGONAL TELLURIUM; NANOTUBES; NANOWIRES; TE; NANOBELTS; NANORODS